Development of Foreign Economic Activity of Enterprises in Modern Conditions - Melnichuk, L. V.; Perets, Ya. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article is devoted to a comprehensive study of the essence and role of foreign economic activity of enterprises in modern conditions. The main approaches to the formation of strategies for the development of foreign economic activity of enterprises are analyzed, it is found that the use of strategies for the development of enterprises in foreign economic activity will not only accelerate the recovery from the crisis by increasing sales volumes in foreign markets, but also allow strengthening competitive positions outside the state. It is found that the development of foreign economic activity of enterprises must be carried out within the framework of national foreign economic policy. It is established that cooperation with state institutions of other countries of the world will ensure the participation of the state in international organizations and associations, which will lead to an increase in the efficiency of foreign economic activity of enterprises.